Use of Balanced Fertilizer Doses and Pruning Methods to Increase Growth and Yield of Rice Plants in Acidic Sulphate Lands in West Borneo - Agus Suyanto; Agusalim Masulili; Setiawan Setiawan; Ismail Astar (The University of Lampung, 2023)
The provision of appropriate technology for farmers was necessary to optimize the productivity of rice plants, especially in acidic sulfate fields. The purpose of study were to determine optimal dose of NPK fertilizer and right pruning time to increase growth and yield of rice plants in acidic sulfate fields. Research was conducted in acidic sulfate fields of Rasau Jaya Tiga village, Kubu Raya district, from August to December 2022. This experiment utilized a factorial randomized design group, with two factors namely: factor I and factor II. Factor I was NPK fertilizer (N): N1 = 0.9 kg/plot, N2 = 1.8 kg/plot, N3 = 2.7 kg/plot, N4 = 4.5 kg/plot. Factor II was leaf pruning (P): P0 = No Pruning, P1 = Pruning 30 days after planting (dap), P2 = Pruning 37 dap, P3 = Pruning 44 dap, P4 = Pruning 51 dap, and P5 = Pruning 58 dap. Observed variables were plant height, number of tillers, number of productive tillers, number of grains per panicle, amount of grain contained per panicle, and dry weight of grain per plot. Data were analyzed using F and Tukey tests at a 5% level of significance. The interaction of pruning treatment and NPK has an unsignificant effect on all observed parameters. NPK treatment and pruning singularly have a significant effect on all observed parameters. Pruning of the plant at 44 dap (P3) and NPK fertilizer dose of 4.5 kg/plot (N4) yielded the best results in all observed variables. Keywords: Acidic Sulphate Lands, Fertilizer, Productivity, Pruning, Rice